General Considerations on the Enforcement (Application) of Law - BERLINGHER, Daniel; SABAU, Georgeta (Journal of Legal Studies, 2016)
Law is a system of norms developed and/or recognized by the state as norms guiding human behaviour according to the values of that particular society, establishing rights and obligations, principles and definitions, structures and relationships of social organization and activity that must be obeyed and which, when necessary, are insured by the coercive force of the state. Thus, the development of this system of norms is not an end in itself, but is intended to regulate all social relations, guide human behaviours and achieve the aims of the law. The enforcement of law is the process of translating legal rules into practice, through which the subjects of law obey and execute legal norms, and state authorities apply them, depending on their competence. The enforcement of law depends on a number of factors that shape law, such as its natural framework of existence, the historical context and the ethnic and national particularities of that community’s development, the economic factor or framework, the framework and particularities of the political system, the cultural-ideological framework or factor, the international framework or factor, etc.